Visitas domiciliarias por actores sociales y su impacto en la reducción de anemia en niñas y niños de 6 a 11 meses del Centro de Salud San Juan de Miraflores 2022 - Camiñas Gómez, Lina Marli (2024)
The objective of the study was to determine the impact of home visits by social actors on the reduction of anemia in girls and boys aged 6-11 months. Methodology: quantitative, analytical, transversal secondary source of data from the Nutritional Status Information System (SIEN) of the MINSA and the mobile application file of home visits by social actors to girls and boys aged 611 months in the Municipality of San Juan Baptist. Information was collected from children who had at least 2 visits in the 6 months period. The first visit was compared with a hemoglobin test and the last visit with a second hemoglobin test. The test of proportions was applied with SPSS v.25 software. Results: 369 children with a diagnosis of Anemia were evaluated, of which 40.4% were moderate anemia. 51.8% were male and 39.8% were 6 months old. 53.9% of the children had complete visits for their age according to current regulations. An increase of 0.6 g/dl in hemoglobin and a reduction in anemia of 34.7% (128/369) was achieved, although the difference was not significant. A significant impact was evident in increasing the control of iron consumption (19.8%) (p< 0.05). Conclusion: A reduction in anemia was evident during the visits of the social actors. Likewise, it was possible to increase healthy practices and control of growth and development.